Impact of the Courtyard Geometry on Cooling Energy Demand in Arid Zones. Univariate Regression-based Approach. - Soufiane Boukarta (Selected Scientific Papers: Journal of Civil Engineering)
Vernacular architecture, often described as architecture without an architect, never ceases to show us the extent to which the building system was linked to its environment and clearly expressed the genius loci. This paper looks at the role that courtyard geometry can play as a thermal and energy regulator in traditional houses. To do this, the study is based on a historical reading of the evolution of the courtyard, with the aim of characterising its geometry in terms of its size in relation to the house, its depth, its position (centred or off-centre), its shape and finally its orientation. To assess the performance of each type of courtyard, the study is based on a campaign of dynamic thermal simulations (DTS) carried out under DesignBuilder for the arid climate of the city of Laghouat in Algeria. The results of the study are based on a comparative approach and modelling using univariate linear regression. The best configuration obtained for the courtyard is that of a rectangular courtyard, with a 10% opening ratio, elongated on the axis east-west direction, a central position and a depth of three levels, as this best combines solar gain and shading protection.